MASYARAKAT YANG KREATIF, INOVATIF, KRITIS DAN BERKARAKTER DI ERA DIGITAL UNTUK MEMBANGUN DAERAH, BANGSA DAN NEGARA - Sarumaha, Martiman S. (Universitas Nias Raya, 2022)
The purpose of this service is to provide understanding to the community, especially the campus community and the wider community who are involved in the academic world. The method of implementing this service is in the form of lectures conveying to the audience how to answer every challenge in facing the growing digital era. In carrying out this service activity a scientific oration was also held at the graduation ceremony at Nias Raya University. As a result of this service, it is hoped that participants from parents, lecturers, postgraduate students and graduates can prepare themselves to answer the needs of society in the digital era, all of which are developing in a more advanced direction. In conclusion, it is hoped that the campus life community can have creative, innovative, critical and character ideas in the digital era to be able to take advantage of every opportunity to improve welfare in the environment where they live.